Biallelic TMEM251 variants in patients with severe skeletal dysplasia and extreme short stature. Issue 1 (30th November 2020) - Ain, Noor U.; Muhammad, Niaz; Dianatpour, Mehdi; Baroncelli, Marta; Iqbal, Muddassar; Fard, Mohammad A. F.; Bukhari, Ihtisham; Ahmed, Sufian; Hajipour, Massoumeh; Tabatabaie, Zahra; Foroutan, Hamidreza; Nilsson, Ola; et al.
Abstract: Skeletal dysplasias are a heterogeneous group of disorders ranging from mild to lethal skeletal defects. We investigated two unrelated families with individuals presenting with a severe skeletal disorder. In family NMD02, affected individuals had a dysostosis multiplex‐like skeletal dysplasia and severe short stature (<−8.5 SD). They manifested increasingly coarse facial features, protruding abdomens, and progressive skeletal changes, reminiscent of mucopolysaccharidosis. The patients gradually lost mobility and the two oldest affected individuals died in their twenties. The affected child in family ID01 had coarse facial features and severe skeletal dysplasia with clinical features similar to mucopolysaccharidosis. She had short stature, craniosynostosis, kyphoscoliosis, and hip‐joint subluxation. She died at the age of 5 years. Whole‐exome sequencing identified two homozygous variants c.133C>T; p.(Arg45Trp) and c.215dupA; p.(Tyr72Ter), respectively, in the two families, affecting an evolutionary conserved gene TMEM251 (NM_001098621.1). Immunofluorescence and confocal studies using human osteosarcoma cells indicated that TMEM251 is localized to the Golgi complex. However, p.Arg45Trp mutant TMEM251 protein was targeted less efficiently and the localization was punctate. Tmem251 knockdown by small interfering RNA induced dedifferentiation of rat primary chondrocytes. Our work implicates TMEM251 in the pathogenesis of a novel disorder and suggests its potential function in chondrocyte differentiation. Abstract : We present two pathogenic alleles of a novel gene TMEM251 as the cause of a severe skeletal dysplasia syndrome in patients from Pakistan and Iran. We show that the green fluorescent protein (GFP) fused wild type protein is localized to the Golgi complex while the GFP fused mutant protein is targeted less efficiently. Small interfering RNA (siRNA) experiments suggested that TMEM251 may have a role in chondrocyte differentiation.